Let "m" be the mass of the particle. The weight of the particle is "mg" and the drag force is "m\\lambda v^2" .
The equation of motion of the particle is
"m\\frac{dv}{dt}=mg-m\\lambda v^2\\\\\n\\Rightarrow \\frac{dv}{dt}=g-\\lambda v^2\\\\\n\\Rightarrow \\frac{dv}{dt}=g(1-\\frac{\\lambda }{g}v^2)\\\\\n\\Rightarrow \\frac{dv}{1-\\frac{\\lambda }{g}v^2}=gdt"
Integrating both sides,
"\\int \\frac{dv}{1-\\frac{\\lambda }{g}v^2}=g\\int dt+C_1\\\\\n\\int \\frac{dv}{1-\\frac{\\lambda }{g}v^2}=gt+C_1\\ \\quad ......(1)"
where "C_1" is the constant of integration.
Let "z=\\sqrt{\\frac{\\lambda}{g}}\\ v\\Rightarrow dz=\\sqrt{\\frac{\\lambda}{g}}\\ dv"
From (1), "\\sqrt{\\frac{g}{\\lambda}}\\int \\frac{dz}{1-z^2}=gt+C_1"
"\\therefore \\sqrt{\\frac{g}{\\lambda}}\\ \\tanh^{-1}(z)=gt+C_1" since "\\int \\frac{dz}{1-z^2}=\\tanh^{-1}(z)"
Substituting "z=\\sqrt{\\frac{\\lambda}{g}}\\ v" ,
"\\sqrt{\\frac{g}{\\lambda}}\\ \\tanh^{-1}\\left(\\sqrt{\\frac{\\lambda}{g}}\\ v\\right)=gt+C_1\\ \\quad .......(2)"
At "t=0, v=0"
"\\Rightarrow \\sqrt{\\frac{g}{\\lambda}}\\ \\tanh^{-1}(0)=0+C_1\\\\\n\\Rightarrow C_1=0" since "\\tanh^{-1}(0)=0"
From (2),
"\\sqrt{\\frac{g}{\\lambda}}\\ \\tanh^{-1}\\left(\\sqrt{\\frac{\\lambda}{g}}\\ v\\right)=gt\\\\\n\\Rightarrow \\tanh^{-1}\\left(\\sqrt{\\frac{\\lambda}{g}}\\ v\\right)=gt\\sqrt{\\frac{\\lambda}{g}}\\\\\n\\Rightarrow \\tanh^{-1}\\left(\\sqrt{\\frac{\\lambda}{g}}\\ v\\right)=\\sqrt{g\\lambda }\\ t\\\\\n\\Rightarrow \\sqrt{\\frac{\\lambda}{g}}\\ v=\\tanh(\\sqrt{g\\lambda }\\ t)\\\\\n\\Rightarrow v=\\sqrt{\\frac{g}{\\lambda}}\\tanh(\\sqrt{g\\lambda }\\ t)\\\\\n\\Rightarrow \\frac{dx}{dt}=\\sqrt{\\frac{g}{\\lambda}}\\tanh(\\sqrt{g\\lambda }\\ t)\\\\\n\\Rightarrow dx=\\sqrt{\\frac{g}{\\lambda}}\\tanh(\\sqrt{g\\lambda }\\ t)dt\\\\"
Integrating,
"x=\\sqrt{\\frac{g}{\\lambda}}\\int \\tanh(\\sqrt{g\\lambda }\\ t)dt+C_2\\ \\quad .......(3)"
where "C_2" is the integration constant.
Let "y=\\sqrt{g\\lambda }\\ t\\Rightarrow dy=\\sqrt{g\\lambda }\\ dt"
From (3),
"x=\\sqrt{\\frac{g}{\\lambda}}\\ \\frac{1}{\\sqrt{g\\lambda }}\\int \\tanh(y)dy+C_2\\\\\n\\Rightarrow x=\\frac{1}{\\lambda} \\int \\tanh(y)dy+C_2\\\\\n\\Rightarrow x=\\frac{1}{\\lambda} \\ln|\\cosh(y)|+C_2" since "\\int \\tanh(y)dy=\\ln |\\cosh(y)|"
Substituting "y=\\sqrt{g\\lambda }\\ t" ,
"x=\\frac{1}{\\lambda} \\ln|\\cosh(\\sqrt{g\\lambda }\\ t)|+C_2\\ \\quad .......(4)"
At "t=0, x=0"
"\\Rightarrow 0=\\frac{1}{\\lambda} \\ln|\\cosh(0)|+C_2"
Since "\\cosh(0)=1 \\ and\\ \\ln(1)=0"
"\\Rightarrow C_2=0"
From (4),
"x=\\frac{1}{\\lambda} \\ln|\\cosh(\\sqrt{g\\lambda }\\ t)|"
Thus, the distance fallen in time "t" is "\\frac{1}{\\lambda} \\ln|\\cosh(\\sqrt{g\\lambda }\\ t)|"
Comments
Leave a comment